2008
DOI: 10.1111/j.1600-0854.2008.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptor Protein Ruk/CIN85 is Associated with a Subset of COPI‐Coated Membranes of the Golgi Complex

Abstract: †These authors contributed equally to this work.Regulator of ubiquitous kinase/Cbl-interacting protein of 85 kDa (Ruk/CIN85) and CD2-associated protein/Cas ligand with multiple SH3 domains (CD2AP/CMS) comprise a family of vertebrate adaptor proteins involved in several important cellular processes, including downregulation of activated receptor tyrosine kinases, regulation of cytoskeletal rearrangements, phosphatidylinositol 3-kinase (PI 3-kinase) signalling and apoptosis. The role of Ruk/CIN85 as a scaffold p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 50 publications
(93 reference statements)
3
29
1
1
Order By: Relevance
“…Accordingly, live-cell imaging illustrated that the majority of endocytosed Glut4 does not traffic back to the plasma membrane, instead remaining in a perinuclear cluster in insulin-stimulated CD2AP −/− podocytes. CD2AP has been shown to colocalize in the perinuclear region with key proteins that participate in the formation of vesicles, including COPI, clathrin and Rab5 (Havrylov et al, 2008). We found that CD2AP co-fractionates in the same subcellular fractions as the GSV markers IRAP, sortilin and Glut4 itself.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Accordingly, live-cell imaging illustrated that the majority of endocytosed Glut4 does not traffic back to the plasma membrane, instead remaining in a perinuclear cluster in insulin-stimulated CD2AP −/− podocytes. CD2AP has been shown to colocalize in the perinuclear region with key proteins that participate in the formation of vesicles, including COPI, clathrin and Rab5 (Havrylov et al, 2008). We found that CD2AP co-fractionates in the same subcellular fractions as the GSV markers IRAP, sortilin and Glut4 itself.…”
Section: Discussionsupporting
confidence: 56%
“…CD2AP is known to colocalize with the endoplasmic reticulum (ER) marker calnexin and the Golgi marker GM130 (also known as GOLGA2) in HeLa cells (Havrylov et al, 2008). This, together with the results of live-cell imaging, led us to investigate whether CD2AP is observed in the same sub-cellular compartments as Glut4 and Glut4 storage vesicle (GSV) markers in WT podocytes.…”
Section: Cd2ap Is Found In the Intracellular Membrane Fractionsmentioning
confidence: 99%
See 2 more Smart Citations
“…4D, right panel (16). Other studies show that CIN85/Ruk L is associated with the Golgi complex, which takes part in membrane trafficking (26,27). We overexpressed CIN85-GFP with ␤1,4-galactotransferase-pDsRed, a Golgi-associated protein, in CD2AP ϩ/ϩ podocyte and stimulated the cells for 60 min with FGF-4.…”
Section: Cd2apmentioning
confidence: 96%